Literature review of modelling approaches for ASR in concrete: a new perspective. Issue 11 (2nd November 2019) - Esposito, R.; Hendriks, M. A. N.
Abstract: The assessment of concrete structures affected by alkali–silica reaction (ASR) is a complex problem due to the multiscale nature of this long-term phenomenon. The reaction starts within the concrete constituents and developed at aggregate level by inducing swelling and deterioration of concrete material, which eventually affect the capacity of the structure. Due to this multiscale nature of the phenomenon, the problem is studied by various researchers in numerous manners. In this paper, a literature review of the main modelling approaches for ASR in concrete is presented within a new perspective. The models are categorised on the basis of their input and output parameters, instead of adopting the classical classification on the base of the scale (e.g. micro, meso and macro). The main aim of the review is to understand to which extent the available models are able to describe the deteriorating impact induced by ASR in concrete material and if the approaches can ultimately be extended to structural analyses.